Features of processing of marine seismic observations using finite-difference full-wave migration - A. O. Verpahovskaya; V. N. Pilipenko; V. P. Kobolev (Геофизический журнал, 2013)
Features and basic principles of plotting the graph of marine seismic observations processing with application of original method of finite-difference total wave migration of the sum of central middle point, which is more stabile in case of investigation of complicated geological sections have been considered. The effectiveness of the method is demonstrated on materials of seismic marine observations performed on the continental slope of northwestern shelf of the Black Sea.